Composite synchronization of three eccentric rotors driven by induction motors in a vibrating system. (1st March 2018) - Kong, Xiangxi; Chen, Changzheng; Wen, Bangchun
Highlights: The model of a vibrating system excited by three eccentric rotors is developed. Composite synchronization is a combination of self- and controlled synchronizations. Composite synchronization of three eccentric rotors is analyzed. Abstract: This paper addresses the problem of composite synchronization of three eccentric rotors (ERs) driven by induction motors in a vibrating system. The composite synchronous motion of three ERs is composed of the controlled synchronous motion of two ERs and the self-synchronous motion of the third ER. Combining an adaptive sliding mode control (ASMC) algorithm with a modified master-slave control structure, the controllers are designed to implement controlled synchronous motion of two ERs with zero phase difference. Based on Lyapunov stability theorem and Barbalat's lemma, the stability of the designed controllers is verified. On basis of controlled synchronization of two ERs, self-synchronization of the third ER is introduced to implement composite synchronous motion of three ERs. The feasibility of the proposed composite synchronization method is analyzed by numerical method. The effects of motor and structure parameters on composite synchronous motion are discussed. Experiments on a vibrating test bench driven by three ERs are operated to validate the effectiveness of the proposed composite synchronization method, including a comparison with self-synchronization method.